The effect of ingredient processing and diet complexity on growth performance of the segregated early-weaned pig - K Hongtrakul; J R Bergstrom; I H Kim; W B Nessmith; Robert D Goodband; Keith C Behnke; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1996)
A 14-day growth trial was conducted to determine the interactive effects of ingredient processing and diet complexity on growth performance of segregated early-weaned pigs. Three processing combinations were used with either a simple or complex diet formulation in 2 x 3 factorial arrangement. Diets were pelleted (control); the corn was moist-extruded, then the complete diet pelleted (extruded); or the complete diet was expanded then pelleted (expanded). An interaction was observed between ingredient processing and diet complexity. Pigs fed the control or extruded diets had improved growth performance as diet complexity increased. However, pigs fed the expanded diets showed little response to increasing diet complexity. Under these experimental conditions, pigs fed moist-extruded corn had the best growth performance. However, further research is warranted to evaluate expander conditioning of complex starter diets.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Segregated early-weaned pigs; Diet complexity; Feed processing